Desenvolvimento de nanocápsulas para a liberação controlada de crisina: avaliação da atividade antioxidante e da citotoxicidade in vitro - Lorenzoni, Alessandra Scherer (2015)
Chrysin (5,7-dihydroxyflavone) is a flavonoid (class of flavones), which presents antioxidant and antitumoral activities. However, it has low solubility and hence its bioavailability in the body is low, limiting its application in the pharmaceutical field. Thus, nanocapsules are alternatives to delivery of this active substance. This study aimed the development of chrysin-loaded nanocapsules (0.3 and 0.75 mg/mL), using ethylcellulose and peanut oil, coconut oil or medium chain triglycerides (MCT), in order to evaluate the antioxidant activity (DPPH assay), in vitro cytotoxicity in normal cells (fibroblasts - 3T3) and tumoral cell lines (breast cancer - MCF-7; SK-MEL-28 melanoma), in view of its therapeutic potentials. The nanocapsule suspensions (0.75 mg/mL) were also lyophilized using trehalose (10% w/v) as cryoprotectant. According to the results, it was possible to prepare nanocapsules containing chrysin with suitable physicochemical characteristics and high encapsulation efficiency. The formulations containing 0.3 mg/ml or 0.75 mg/ml of chrysin were stable for 30 days or 50 days, respectively, considering the average particle diameter and polydispersion indexes (PdI). However, the chrysin content decreased after 30 days. All formulations were able to control release of chrysin in relation to the diffusion of this flavonoid in methanolic solution, in buffer acetate pH 5.0: ethanol (70:30). The chrysin-loaded nanocapsule suspensions showed increase in antioxidant activity as following: peanut oil, coconut oil, and MCT. Considering the in vitro cytotoxicity, all developed nanocapsule suspensions (with chrysin or without) did not show cytotoxicity in fibroblasts. The chrysin-loaded nanocapsules showed antiproliferative activity in breast cancer cells and melanoma at dose-dependent manner. Also, there was the influence of the type of endpoint (MTT or NRU), suggesting differences between the possible mechanisms of toxicity. In breast cancer cells, it is suggested that an initial effect can occur on the metabolic and mitochondrial activity of the cell and, in a second step, the membrane integrity and lissosomal activity can be affected. For the melanoma cells, the contrary mechanism can be observed. The nanocapsules without chrysin were also cytotoxic to tumoral cells, depending on both the concentration of the assay and the endpoint test. Moreover, it was possible to obtain dispersible dried products from freeze-drying of nanocapsule suspensions. Analysis by electron microscopy revealed the presence of colloidal spherical structures after lyophilization. The dried products showed stable chrysin content during 50 days of the study. Considering these results, the ethylcellulose nanocapsules containing chrysin are interesting intermediate systems that can be used in future treatments, due to its antioxidant and antiproliferative activities.